THE PORTRAIT OF MARRIAGE IN VICTORIAN ERA IN JANE AUSTEN’S PERSUASION - Ratih Ajeng Oktorina; Eko Budi Setiawan; Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2017)
The aim of this research is to discuss the portrait of marriage in Victorian era in Jane Austen’sPersuasion. This is a library research in which all the data and the theories are taken fromwritten form which is related to the portrait of marriage in Victorian era including internetbrowsing to support the data. The theories of marriage, and setting are applied to analyze thedata. There are two approaches used to analyze the data. The first approach is sociologicalapproach and the second approach is historical-biographical. The research proves that theportrait of marriage in Victorian era is portrayed in Jane Austen’s Persuasion through thecharacters in that novel. At that time, marriage is the way for getting social status. Women inVictorian era will find men with the large fortune to become their husband. Meanwhile,marriage for love happens rarely.